Analisis Peer to Peer Lending dan CrowdFunding pada Fintech Syariah Ditinjau dari Fatwa DSN MUI dan Pendekatan Maqashid Syariah - Ika Rarawahyuni; Via Rismaya (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
Peer to peer lending and crowdfunding is a type of fintech used by sharia fintechs that utilize technology services. The purpose of this study (1) Analyzing the suitability of peer to peer lending and crowdfunding mechanisms in sharia fintech with the provisions of the Fatwa DSN MUI No: 117 / DSN-MUI / II / 2018 concerning information technology-based financing services based on sharia principles (2) Analyzing peer to mechanism peer lending and crowdfunding with maqashid sharia approach. The method used in this research is a qualitative library with 3 stages of orientation, exploration and focused study. The results of this study indicate that the mechanism used by peer to peer lending in sharia fintech is in accordance with Fatwa DSN MUI No: 117 / DSN-MUI / II / 2018 about information technology-based financing services based on sharia principles and if it is appropriate then maqashid is achieved so that it is achieved prosperous life in the world and the hereafter. For crowdfunding researchers did not find a mechanism on fintech registered with OJK, the researchers found a mechanism that can be used corwdfunding on sharia fintech, after analysis is in accordance with the Fatwa DSN MUI. However, there is one financing model that does not comply with the Fatwa DSN MUI because it still determines the margin determined unilaterally.